Graphene: Synchronous Growth of High‐Quality Bilayer Bernal Graphene: From Hexagonal Single‐Crystal Domains to Wafer‐Scale Homogeneous Films (Adv. Funct. Mater. 22/2017). (June 2017) - Wu, Jun; Wang, Junyong; Pan, Danfeng; Li, Yongchao; Jiang, Chenghuan; Li, Yingbin; Jin, Chen; Wang, Kang; Song, Fengqi; Wang, Guanghou; Zhang, Hao; Wan, Jianguo
Abstract : Bilayer graphene is important for device applications due to its tunable band gap. In article number1605927, Jianguo Wan and co‐workers report a method to rapidly synthesize bilayer Bernal graphene by atmospheric pressure chemical vapor deposition using polystyrene as the feedstock. A high surface coverage of nearly 100% for a near‐perfect AB stacking order is achieved.